If you know that -2 is a zero of f(x) = x^3 + 7x^2 + 4x - 12, explain how to solve the equation.
First you have to figure out what could make f(x) = 0 to get rid of the cube. I'm going to test the array of data, x = -2, x = -3, and x = -4 because this type of equation probably has more negative values given that if you plug in some values the cubed-values and squared-values will surpass the "-12". Plug this into a calculator.
x^3 + 7x^2 + 4x - 12
f(-2) = -8 + 28 - 8 - 12 = 0
So you know that when x = -2, f(x) = 0. Divide "(x + 2)" from the equation and you will get... x^2 + 5x - 6. Now this is a simple polynomial one that you can figure to be (x + 6) (x - 1) just by looking at it because -6 multiplied by 1 is negative 6 and you see 5 and know that 6 - 1 = 5.
The solution is (x + 6) (x - 1) (x + 2) meaning that when x = -6, 1, or -2, f(x) is 0.
2+3+8
3+8+2
3+2+8
8+2+3
8+3+2
there are multiple ways to get the same sum with the same three numbers i hope this helps
A.
If you solve it all out you get f(x)= -4x^2 -56x-202
Answer:
11
Step-by-step explanation:
f(x)=3x+8
f(1)=3(1)+8
f(1)=3+8
f(1)=11
Answer:
Congruent angles and proportional side lengths
Step-by-step explanation: